GOVERNANCE FAILURE AS A TRIGGER OF FRAUD IN INVESTMENT MANAGEMENT: A CASE STUDY OF PT ASABRI - Fitri Nurhayati M; Tiara Abdurahman; Sahmin Noholo (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to analyze how governance failure became a trigger for fraud in investment management at PT ASABRI. The research employs a literature study approach. The results indicate that fraud at PT ASABRI was driven by the weak implementation of corporate governance principles, particularly in terms of transparency, accountability, and independence. In addition, violations of the prudential principle and weak internal controls led to investment decisions being made without adequate risk considerations and opened opportunities for collusion between internal and external parties of the company. The findings of this study emphasize that fraud is a direct consequence of governance system failure rather than merely the actions of individuals. Therefore, this study recommends the need for comprehensive governance reform through strengthening risk management, enhancing the transparency of investment reporting, and implementing independent oversight mechanisms to prevent similar cases in the future.